Bioenergy and biofuel from biowastes and biomass - Khanal, Samir Kumar (American Society of Civil Engineers, 2010)
Biofuel and bioenergy produced from biowastes and biomass is a clean energy source which can be produced renewably. The 21 chapters of this book provide state-of-the-art reviews, current research, and technology developments with respect to 1st, 2nd, and 3rd generation biofuels and bioenergy. The book focuses on the biological/ biochemical pathway, as this option has been reported to be the most cost-effective method for biofuel/bioenergy production. The opening chapter covers the overview of the current status of biofuel and bioenergy production. The rest of the chapters are grouped into seven categories; they cover biomethane production, microbial fuel cells, feedstock production, preprocessing, biomass pretreatment, enzyme hydrolysis, and syngas fermentation. Algal processes for biofuel production, biobutanol production, bioreactor systems, and value-added processing of biofuel residues are included. This book addresses life cycle analyses (LCA) of 1st and 2nd generation.